Multi-temporal airborne laser scanning raster data from Findelengletscher, Valais, Switzerland, 2005-2010 - Joerg, Philip Claudio; Morsdorf, Felix; Zemp, Michael (Supplement to: Joerg, PC et al. (2012): Uncertainty assessment of multi-temporal airborne laser scanning data: A case study on an Alpine glacier. Remote Sensing of Environment, 127, 118-129, https://doi.org/10.1016/j.rse.2012.08.012, 2018)
This dataset contains multi-temporal raster geotiff data of the Findelengletscher, Valais, Switzerland (46° N, 7° 52' E), documenting the glacier change in the period 2005-2010. The data is available in the Swiss datum CH1903 (LV03). Elevations are in meters in the Swiss LN02. The spatial resolution is one meter. The airborne laser scanning (LiDAR) point cloud data was interpolated into a raster grid in Matlab (average of point elevations per grid cell). Empty cells were interpolated using a least squares method without changing known values. Moreover, the extrapolation behavior was linear. There are four data sets available, from October 28/29, 2005; October 4, 2009; April 10, 2010 and September 29, 2010.